IMPROVEMENT OF INDONESIAN LANGUAGE LEARNING THROUGH COOPERATIVE LEARNING MODEL TYPE-JIGSAW WITH PICTURE MEDIA AT SDN PUCUKSARI CLASS III KENDAL REGENCY - Gatot, Masitowati; Agtriyanti, Reni (Program Studi PGMI, 2025)
The learning outcomes of third-grade Indonesian Language students at Pucuksari Elementary School, Kendal Regency, were low, as evidenced by daily test data. Most students scored below the Minimum Passing Criteria (KKM ≥ 75), with only a few exceeding this threshold. Teaching methods were primarily teacher-centered and lacked diversity in instructional media, leading to low student engagement. To address these challenges, action research was conducted in the classroom using a jigsaw cooperative learning model supplemented with visual media.The study aimed to evaluate the effectiveness of this model in enhancing teacher skills, student activities, and learning outcomes in Indonesian Language lessons. The research design comprised two cycles, each involving planning, implementation, observation, and reflection. The participants were 23 third-grade students—12 boys and 11 girls—from Pucuksari Elementary School. Data collection techniques included both non-test methods (observation, interviews, field notes, documentation) and test methods (written assessments). Findings revealed significant improvement in student engagement and learning outcomes, particularly in topics related to transportation technology. Achievement rates increased from 67% in Cycle I to 88% in Cycle II. Similarly, learning mastery rose from 55% with 9 students meeting criteria in Cycle I to 95% with 22 students achieving success in Cycle II. Conclusively, the implementation of the jigsaw cooperative learning model with pictorial media substantially enhanced student activities and learning outcomes. Teachers are encouraged to adopt this model to create more dynamic and engaging learning environments, yielding better academic results for students.